Chemical modification of bradykinin-polymer conjugates for optimum delivery of nanomedicines to tumors - Appiah, Enoch; Nakamura, Hideaki; Assumang, Anthony; Etrych, Tomáš; Haratake, Mamoru (Nanomedicine, 2024)
We recently prepared pH-responsive HPMA copolymer conjugates of bradykinin (P-BK), which release BK in response to the acidic tumor microenvironment, and found that administration of P-BK increased the tumor accumulation and therapeutic efficacy of nanomedicine. Because the release of BK from P-BK determines its onset of action, P-BKs with different release rates were prepared, and their properties were evaluated. The release kinetics were significantly altered by substitution proximal to hydrazone bond, release constant of methyl-substituted P-BK (P-MeBK) was approximately 4- and 80-fold higher than that of cyclopropyl-substituted P-BK (P-CPBK) and phenyl-substituted P-BK (P-PhBK). None of the P-BKs were active, but the release of BK restored their BK-like activity. Pre-administration of the P-BKs increased the tumor accumulation of nanomedicine in C26 tumor-bearing mice by 2- and 1.4-fold for P-MeBK and P-PhBK at 3 and 6 h. Altogether, this study provides insights into the design of pH-responsive nanodrugs with the desired release properties to target acidic lesions such as cancer and inflammation.
Keywords: Controlled release; nanomedicína; HPMA polymer; Nanomedicine; doxorubicin; Doxorubicin; zvířata; myši; Mice; polymery; Polymers; Bradykinin; Neoplasms; Hydrogen-Ion Concentration; Tumor Microenvironment; bradykinin; nádory; nádorové mikroprostředí; Animals; koncentrace vodíkových iontů; Hydrazone; Tumor